2017
DOI: 10.1093/infdis/jix361
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Infectiousness and Host Susceptibility

Abstract: The transmission of tuberculosis is complex. Necessary factors include a source case with respiratory disease that has developed sufficiently for Mycobacterium tuberculosis to be present in the airways. Viable bacilli must then be released as an aerosol via the respiratory tract of the source case. This is presumed to occur predominantly by coughing but may also happen by other means. Airborne bacilli must be capable of surviving in the external environment before inhalation into a new potential host—steps inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
7

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 85 publications
0
58
0
7
Order By: Relevance
“…Our Respiratory Aerosol Sampling Chamber (RASC) effectively functions as a personal clean-room, enabling collection and concentration of particulate material released by an individual patient during normal respiratory activity, including from natural (non-induced) cough (29,37). Through multiple iterations informed by our preliminary experimental and clinical observations, we have equipped the RASC to address systematically the comprehensive TB transmission research agenda outlined by others (38). Key questions posed include: When are viable, infection-competent bacilli released by Mtb-infected individuals?…”
Section: Introductionmentioning
confidence: 99%
“…Our Respiratory Aerosol Sampling Chamber (RASC) effectively functions as a personal clean-room, enabling collection and concentration of particulate material released by an individual patient during normal respiratory activity, including from natural (non-induced) cough (29,37). Through multiple iterations informed by our preliminary experimental and clinical observations, we have equipped the RASC to address systematically the comprehensive TB transmission research agenda outlined by others (38). Key questions posed include: When are viable, infection-competent bacilli released by Mtb-infected individuals?…”
Section: Introductionmentioning
confidence: 99%
“…Torres-Gonzalez et al 29 , for example, found a high prevalence of latently infected dairy farm and abattoir workers in a high bTB cattle prevalence district of Mexico associated with occupational exposure. The factors affecting latency, and reversion to active disease, are complex and poorly understood for TB 30,31 , reducing our capabilities to project future infection outcomes. Neither should there be assumptions that M. bovis could not in future emerge as a more virulent pathogen than to date through the emergence of new strains, or the Pre-print accepted version: Veterinary Record -July 2019 21 possibility that newly emerging co-infections or co-morbidities such as diabetes mellitus could not change the epidemiology and pathophysiology of M. bovis infection in humans, making it a more prevalent and fearsome proposition.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, regulatory T cells (Tregs) may inhibit protective immunity. 5,6 Theoretically, each of these pathways constitutes potential and 'druggable' targets. However, this notion is complicated by the complex course of progressive TB disease, including stages such as initial infection, protracted latency and overt disease 7,8 Furthermore, other factors such as genetic diversity and co-morbidities (e.g.…”
Section: Introductionmentioning
confidence: 99%